23.0k views
1 vote
What is the simplified expression for

What is the simplified expression for-example-1
What is the simplified expression for-example-1
What is the simplified expression for-example-2
User Price
by
5.4k points

1 Answer

6 votes

Answer:

The simplified expression for
(3^(-4) * 2^(3) * 3^(2))/(2^(4) * 3^(-3)) is
(3)/(2)

Solution:

The given equation is
(3^(-4) * 2^(3) * 3^(2))/(2^(4) * 3^(-3))

Simplifying the equation we get,


(3^(-4) * 2^(3) * 3^(2))/(2^(4) * 3^(-3))


\Rightarrow (\left(3^(-4) * 3^(2)\right) * 2^(3))/(2^(4) * 3^(-3))

Simplifying the exponential form,


\Rightarrow (3^(-4+2) * 2^(3))/(2^(4) * 3^(-3))


\Rightarrow (3^(-2) * 2^(3))/(2^(4) * 3^(-3))


\Rightarrow\left((3^(-2))/(3^(-3))\right) *\left((2^(3))/(2^(4))\right)


\Rightarrow 3^(-2+3) * 2^(3-4)


\Rightarrow 3^(1) * 2^(-1)

On simplifying the exponential form we get,


\Rightarrow (3)/(2)